(3ZGjI GdEJbGf aj JOHjQ HOf GdEfSGfs - (3UGdM Hf fUQ Hf Sdhe GdMdHj,J (B1081 (3g` s ((3GdMdHj GdeSjMj s)
(3ChdgG (B:s
(3hHYO adeG cGf Yde GdWH HMQkG dGjOQc dg bQGQ, hJjgkG hGSYkG dGjTb dg ZHGQ hbO nOhf aj CUhdg haQhYg GdCSGWjQ ef MceGA GdjhfGf hGWHGA GddGJjf eGdG jYO hdGojMUi ef GdCSaGQ s
(3BNQgG (B:s
(3hjSbj gPg GdHGO RgQGJ GdePchQI CQHYjf jhekG MJi jDef GdNha ef GdeGA , EPG TQH CcKQ ef Pdc cGf UhGHkG Je GdcJGH HYhf Gdedc GdhgGH s
(3QJHg hdOg jMji GdeJhai SfI (B1117 (3g`s
(3hjTJed Ydi CQHYeGFI hSHY hCQHYjf aUdkGs
(3fSNI KGfjIs
(3fSNI Yf fSNI HNW GdeDda s
(3JGQjN fSNgG SfI (B1706(3es
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs